Identifikasi Usia Piutang pada Hotel XYZ - Chandrawati Dasuba; R. Muh. Syah Arief Atmaja Wijaya (Masyarakat Ekonomi Syariah Bogor, 2024)
The hospitality industry is a dynamic and competitive sector where financial management efficiency is key to business success and sustainability. Hotel XYZ, as one of the leading hotels in Surabaya, faces various financial challenges, especially in the management of receivables. This study aims to identify the management of accounts receivable management in overcoming accounts receivable problems based on the age of accounts receivable at the hotel. The research method used is a qualitative approach with a case study at Hotel XYZ. Primary data was obtained through interviews with hotel management and finance staff, while secondary data was obtained from financial reports and related literature. The results showed that effective receivables management can strengthen cash flow, and liquidity.